Growth of Nannochloropsis oculata Cultured using Tofu Liquid Waste Fertilizer - Rahmadan, Rizky Yanuar; Satyantini, Woro Hastuti; Sari, Luthfiana Aprilianita (PT Inovasi Pratama Internasional, 2025)
Growth of Nannochloropsis oculata is affected by nutrients in its culture media. Tofu liquid waste which is processed into fertilizer is expected to be an alternative nutrient that is more economical for microalgae culture activities. The purpose of this study was to determine the effect of tofu liquid waste fertilizer with different concentrations on the growth of Nannochloropsis oculata. This study used an experimental method with Completely Randomized Design (CRD). The treatment was different concentrations namely P1 (1 ml L-1), P2 (3 ml L-1), P3 (5 ml L-1), P4 (7 ml L-1) and P0 (Walne nutrient 1 ml L-1) each treatment were repeated four times. The main parameters in this study were cell density, cell growth rate and cell doubling time. Data obtained were analyzed using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT). Results showed that the treatment of tofu liquid waste fertilizer with different concentrations had a significant different (p<0,05) on the growth of Nannochloropsis oculata. Concentration of 5 ml L-1 (P3) was the best concentration for the growth of Nannochloropsis oculata with peak cell density 1,335±13.54x104 cells ml-1, cell growth rate 0.900±0.001 cells ml-1 day-1 and cell doubling time 18.493±0.026 hours.